Resin composition, pellet, and molded article
The resin composition with polyolefin wax and brominated flame retardant addresses the challenge of high-temperature glow time in polyalkylene terephthalate and styrene resins, enhancing mold releasability and mechanical strength without fluoropolymers.
Patent Information
- Application Number
- JP2023107208
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Existing resin compositions containing polyalkylene terephthalate and styrene resins face challenges in achieving reduced glow time under high temperatures without using fluoropolymers, which are regulated under the Stockholm Convention on Persistent Organic Pollutants, and require improved heat resistance and mechanical strength.
A resin composition is developed that includes polyolefin wax and a brominated flame retardant, with specific ratios of polyalkylene terephthalate and styrene resins, to enhance mold releasability and reduce glow time, while avoiding fluoropolymers.
The composition achieves a shorter glow time under high temperatures and improved mold releasability, maintaining mechanical strength and heat resistance without using fluoropolymers.
Smart Images

Figure 2025006421000001 
Figure 2025006421000002 
Figure 2025006421000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a pellet, and a molded article, and in particular to a resin composition containing a polyalkylene terephthalate resin and a styrene-based resin as main components. [Background technology]
[0002] Polyalkylene terephthalate resins, typified by polybutylene terephthalate resin and polyethylene terephthalate resin, are excellent in mechanical strength, chemical resistance, electrical insulation, and the like, and are therefore widely used in electrical and electronic equipment parts, automotive interior and exterior parts, other electrical parts, machine parts, and the like. In order to improve the warpage resistance, heat resistance and mechanical strength of molded articles made from polybutylene terephthalate resin, it has been considered to blend a styrene-based resin. Specifically, Patent Document 1 describes a method for blending a styrene-based resin with a polybutylene terephthalate resin having an intrinsic viscosity (IV) of 0.3 to 0.8 dL / g in an amount of 10 to 50 parts by mass, and a styrene-based resin having an intrinsic viscosity (IV) of 250°C, 912 sec. -1 The present invention discloses a thermoplastic resin composition comprising 50 to 90 parts by mass of a polystyrene resin or a rubber-reinforced polystyrene resin having a melt viscosity of 80 to 500 Pa sec at 20° C., and, relative to a total of 100 parts by mass of the above and (B), 10 to 50 parts by mass of (C) a brominated flame retardant and 0.1 to 30 parts by mass of (D) an antimony compound. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-176158 A Summary of the Invention [Problem to be solved by the invention]
[0004] Although the above-mentioned resin composition is an excellent material, depending on the application, etc., a shorter glowing time is required. In particular, a shorter glowing time is required when the composition is left at a high temperature for a long time. Meanwhile, in recent years, organic fluorine compounds have become regulated or candidates for regulation under the Stockholm Convention on Persistent Organic Pollutants and the like. In flame-retardant resin compositions, fluoropolymers are widely used as anti-dripping agents, but a flame-retardant resin composition that achieves flame retardancy without blending fluoropolymers is required. The present invention aims to solve such problems, and to provide a resin composition that is substantially free of fluoropolymers and that can provide a molded article with a shorter glowing time when placed under high temperatures for a long period of time, as well as a pellet and a molded article. [Means for solving the problem]
[0005] In view of the above-mentioned problems, the present inventors have conducted research and have found that, by blending a polyolefin wax together with a flame retardant in a resin composition containing a polyalkylene terephthalate resin and a styrene-based resin, the above-mentioned problems can be solved even in a resin composition that does not substantially contain a fluoropolymer. Specifically, the above problems were solved by the following means. <1> A resin composition comprising 10 to 90 parts by mass of a polyalkylene terephthalate resin and 90 to 10 parts by mass of a styrene-based resin, for a total of 100 parts by mass, 0.5 to 45 parts by mass of a flame retardant and 0.01 to 10 parts by mass of a polyolefin wax, and substantially no fluoropolymer. <2> The polyalkylene terephthalate resin has an intrinsic viscosity of 0.40 to 1.2 dL / g. <1> The resin composition according to claim 1. <3> The polyalkylene terephthalate resin has an intrinsic viscosity of 0.40 to 0.85 dL / g. <1> The resin composition according to claim 1. <4> The intrinsic viscosity of the polyalkylene terephthalate resin is 0.40 to 0.80 dL / g. <1> The resin composition according to claim 1. <5> The polyalkylene terephthalate resin comprises a polybutylene terephthalate resin. <1> ~ <4> 10. The resin composition according to claim 9 . <6> The flame retardant comprises a brominated flame retardant. <1> ~ <5> 10. The resin composition according to claim 9 . <7> The polyolefin wax comprises a polyethylene wax. <1> ~ <6> 10. The resin composition according to claim 9 . <8> Further comprising a compatibilizer, <1> ~ <7> 10. The resin composition according to claim 9 . <9> The compatibilizer comprises a polycarbonate resin. <8> The resin composition according to claim 1. <10> The polyalkylene terephthalate resin has an intrinsic viscosity of 0.40 to 0.80 dL / g; the polyalkylene terephthalate resin comprises a polybutylene terephthalate resin; The flame retardant comprises a brominated flame retardant, The polyolefin wax comprises a polyethylene wax, Further comprising a compatibilizer, The compatibilizer comprises a polycarbonate resin. <1> ~ <9> 10. The resin composition according to claim 9 . <11> <1> ~ <10> 2. A pellet of the resin composition according to claim 1. <12> <1> ~ <10> 2. A molded article formed from the resin composition according to claim 1. <13> <11> A molded article formed from the pellets according to claim 1. Effect of the Invention
[0006] According to the present invention, it is possible to provide a resin composition that is substantially free of a fluoropolymer and that can provide a molded article with a shorter glowing time when placed under high temperatures for a long period of time, as well as a pellet and a molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values are those at 23° C. unless otherwise specified. If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated.
[0008] The resin composition of the present embodiment is characterized in that it contains 0.5-45 parts by mass of a flame retardant and 0.01-10 parts by mass of a polyolefin wax, relative to a total of 100 parts by mass of 10-90 parts by mass of a polyalkylene terephthalate resin and 90-10 parts by mass of a styrene-based resin, and is substantially free of a fluoropolymer. By adopting such a constitution, a resin composition that is substantially free of a fluoropolymer and can provide a molded product with a shorter glowing time when placed under high temperature for a long period of time can be obtained. Furthermore, a resin composition with excellent releasability can be obtained. The reason for this is presumably due to the use of polyolefin wax as a release agent. That is, polyolefin wax has a relatively large molecular weight as a release agent. Therefore, it is presumed that the amount of low molecular weight components that are likely to remain as fire sources in the resin composition derived from the release agent is reduced, and the glowing time can be shortened. In particular, it is assumed that the glowing time can be effectively shortened when the resin composition is left at high temperatures for a long period of time. Furthermore, in the resin composition of the present embodiment, when a polyolefin wax is used, a composition having even better releasability can be obtained. The present invention will be described in detail below.
[0009] <Polyalkylene terephthalate resin> The resin composition of the present embodiment contains a polyalkylene terephthalate resin. The polyalkylene terephthalate resin is a polyester obtained by, for example, polycondensation of terephthalic acid as a dicarboxylic acid compound and a diol, and may be either a homopolyester or a copolyester.
[0010] As the dicarboxylic acid compound constituting the polyalkylene terephthalate resin, a terphthalic acid compound or an ester-forming derivative thereof is preferably used. Aromatic dicarboxylic acids other than terephthalic acid can also be used in combination. Examples of such dicarboxylic acids include isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-3,3'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, diphenylether-4,4'-dicarboxylic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, diphenylisopropylidene-4,4'-dicarboxylic acid, 1,2-bis(phenoxy)ethane-4,4'-dicarboxylic acid, anthracene-2,5-dicarboxylic acid, anthracene-2,6-dicarboxylic acid, p-terphenylene-4,4'-dicarboxylic acid, and pyridine-2,5-dicarboxylic acid. These can be used in the polycondensation reaction as ester-forming derivatives such as dimethyl esters in addition to free acids. Of the above, isophthalic acid or its ester-forming derivatives are particularly preferred.
[0011] In addition, one or more aliphatic dicarboxylic acids such as adipic acid, azelaic acid, dodecanedioic acid, and sebacic acid, and alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid can be mixed and used in small amounts together with terephthalic acid and the above-mentioned aromatic dicarboxylic acids.
[0012] Examples of dihydroxy compounds constituting the polyalkylene terephthalate resin include aliphatic diols such as ethylene glycol, propylene glycol, butanediol, hexylene glycol, neopentyl glycol, 2-methylpropane-1,3-diol, diethylene glycol, and triethylene glycol, alicyclic diols such as cyclohexane-1,4-dimethanol, and mixtures thereof. Among these, butanediol and ethylene glycol are particularly preferred.
[0013] In addition, one or more long-chain diols having a molecular weight of 400 to 6,000, such as polyethylene glycol, poly-1,3-propylene glycol, polytetramethylene glycol, etc. may be copolymerized. In addition, aromatic diols such as hydroquinone, resorcinol, naphthalene diol, dihydroxydiphenyl ether, and 2,2-bis(4-hydroxyphenyl)propane may also be used.
[0014] In addition to the above-mentioned bifunctional monomers, a small amount of a trifunctional monomer such as trimellitic acid, trimesic acid, pyromellitic acid, pentaerythritol, or trimethylolpropane may be used in combination to introduce a branched structure, or a monofunctional compound such as a fatty acid may be used in combination to adjust the molecular weight.
[0015] The polyalkylene terephthalate resin is preferably one that is mainly composed of polycondensation of terephthalic acid and diol, i.e., one that is composed of this polycondensate in an amount of more than 50% by mass of the entire resin, preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, still more preferably 95% by mass or more, and even more preferably 99% by mass or more. The diol is preferably an aliphatic diol, more preferably 1,4-butanediol or ethylene glycol, and more preferably 1,4-butanediol.
[0016] The amount of terminal carboxyl groups of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) may be appropriately selected and determined, but is usually 60 eq / ton or less, preferably 50 eq / ton or less, and more preferably 30 eq / ton or less. By making it 60 eq / ton or less, gas generation during melt molding of the resin composition tends to be more effectively suppressed. The lower limit of the amount of terminal carboxyl groups is not particularly set, but is usually 3 eq / ton or more, preferably 5 eq / ton or more, and more preferably 10 eq / ton or more.
[0017] The amount of terminal carboxyl groups in the polyalkylene terephthalate resin is a value measured by dissolving 0.5 g of the resin in 25 mL of benzyl alcohol and titrating it with a 0.01 mol / L benzyl alcohol solution of sodium hydroxide. The amount of terminal carboxyl groups can be adjusted by any conventional method, such as adjusting the polymerization conditions such as the raw material charge ratio during polymerization, the polymerization temperature, and the pressure reduction method, or by reacting a terminal blocking agent.
[0018] The intrinsic viscosity of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) is preferably 0.40 dL / g or more, more preferably 0.50 dL / g or more, even more preferably 0.55 dL / g or more, even more preferably 0.60 dL / g or more, and even more preferably 0.65 dL / g or more. By making it equal to or more than the lower limit, there is a tendency that the deterioration of physical properties such as strength can be effectively suppressed. In addition, the intrinsic viscosity of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) is preferably 1.2 dL / g or less, more preferably 0.85 dL / g or less, even more preferably 0.80 dL / g or less, even more preferably 0.75 dL / g or less, and even more preferably 0.72 dL / g or less. By making it equal to or less than the upper limit, there is a tendency that the deterioration of fluidity can be effectively suppressed, and by adjusting the blend ratio with the styrene-based resin, the deterioration of the deflection temperature under load can be more effectively suppressed.
[0019] The intrinsic viscosity is measured by the following method. Polyalkylene terephthalate resin pellets are dissolved in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (mass ratio 1 / 1) by stirring at 110°C for 1 hour to a concentration of 1.00 g / dL. The solution is then cooled to 30°C. The time it takes for the sample solution and the solvent alone to fall at 30°C is measured using a fully automatic solution viscometer, and the intrinsic viscosity is calculated using the formula: Intrinsic viscosity=((1+4K H η sp ) 0.5 -1) / (2K H C) Here, η sp = η / η0-1, where η is the time it takes for the sample solution to fall, η0 is the time it takes for the solvent alone to fall, C is the concentration of the sample solution (g / dL), and K H is Huggins' constant. K H was set to 0.33. The fully automatic solution viscometer used is a product of Shibayama Scientific Co., Ltd. When the resin composition of the present embodiment contains two or more types of polyalkylene terephthalate resins, the intrinsic viscosity is the intrinsic viscosity of the mixture.
[0020] The preferred polyalkylene terephthalate resin is one in which 95 mol % or more of the acid component is terephthalic acid and 95 mol % or more of the alcohol component is an aliphatic diol, and representative examples thereof are polybutylene terephthalate resin and polyethylene terephthalate resin. These are preferably close to homopolyesters, that is, 95 mol % or more of the entire resin is composed of terephthalic acid components and 1,4-butanediol or ethylene glycol components. The polyalkylene terephthalate resin is preferably a polybutylene terephthalate resin and / or a polyethylene terephthalate resin. Among them, the polyalkylene terephthalate resin preferably contains polybutylene terephthalate resin as a main component, and more than 50% by mass of the polyalkylene terephthalate resin is preferably polybutylene terephthalate resin. In this case, it is also preferable that the content of polyethylene terephthalate resin is less than 50% by mass.
[0021] Polybutylene terephthalate resin can be produced by batch or continuous melt polymerization of a dicarboxylic acid component mainly composed of terephthalic acid or an ester derivative thereof and a diol component mainly composed of 1,4-butanediol. After producing a low molecular weight polybutylene terephthalate resin by melt polymerization, the degree of polymerization (or molecular weight) can be increased to a desired value by further solid-phase polymerization under a nitrogen gas flow or reduced pressure.
[0022] The polybutylene terephthalate resin is preferably produced by a continuous melt polycondensation process of a dicarboxylic acid component mainly composed of terephthalic acid and a diol component mainly composed of 1,4-butanediol.
[0023] The catalyst used in carrying out the esterification reaction may be a conventionally known catalyst, and examples thereof include titanium compounds, tin compounds, magnesium compounds, calcium compounds, etc. Among these, titanium compounds are particularly preferred. Specific examples of titanium compounds as esterification catalysts include titanium alcoholates such as tetramethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate, and titanium phenolates such as tetraphenyl titanate.
[0024] The polybutylene terephthalate resin may be a polybutylene terephthalate resin modified by copolymerization (hereinafter, also referred to as a "modified polybutylene terephthalate resin"), and specific preferred copolymers include polyester ether resins copolymerized with polyalkylene glycols (particularly polytetramethylene glycol), dimer acid copolymerized polybutylene terephthalate resins, and isophthalic acid copolymerized polybutylene terephthalate resins.
[0025] When a polyester ether resin copolymerized with polytetramethylene glycol is used as the modified polybutylene terephthalate resin, the proportion of the tetramethylene glycol component in the copolymer is preferably 3 to 40 mass%, more preferably 5 to 30 mass%, and even more preferably 10 to 25 mass%. When a dimer acid copolymerized polybutylene terephthalate resin is used as the modified polybutylene terephthalate resin, the proportion of the dimer acid component in the total carboxylic acid components is preferably 0.5 to 30 mol %, more preferably 1 to 20 mol %, and even more preferably 3 to 15 mol %, in terms of carboxylic acid groups. When an isophthalic acid copolymerized polybutylene terephthalate resin is used as the modified polybutylene terephthalate resin, the proportion of isophthalic acid components in all carboxylic acid components is preferably 1 to 30 mol %, more preferably 1 to 20 mol %, and even more preferably 3 to 15 mol %, in terms of carboxylic acid groups. Among the modified polybutylene terephthalate resins, polyester ether resins copolymerized with polytetramethylene glycol and isophthalic acid copolymerized polybutylene terephthalate resins are preferred.
[0026] The content of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) in the resin composition of this embodiment is preferably 10% by mass or more, more preferably 15% by mass or more, in 100% by mass of the resin composition. The content of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) is preferably 40% by mass or less, more preferably 35% by mass or less, and even more preferably 30% by mass or less, and may be 25% by mass or less, 20% by mass or less, depending on the application. The resin composition of the present embodiment may contain only one type of polyalkylene terephthalate resin (preferably polybutylene terephthalate resin), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0027] <Styrene-based resin> The resin composition of the present embodiment contains a polystyrene-based resin. The polystyrene resin in the present embodiment may be a homopolymer of a styrene monomer, a copolymer of a styrene monomer and a monomer copolymerizable with the styrene monomer, etc. In the copolymer of a styrene monomer and a monomer copolymerizable with the styrene monomer, it is preferable that 50% by mass or more of the total monomers are styrene monomers, more preferably 60% by mass or more, and more preferably 100% by mass or less are styrene monomers.
[0028] The styrene-based monomer means styrene and styrene having a substituent, and examples thereof include styrene, α-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, p-tert-butylstyrene, vinylnaphthalene, methoxystyrene, monobromostyrene, dibromostyrene, fluorostyrene, tribromostyrene, and the like. Styrene and α-methylstyrene are more preferable, and styrene is particularly preferable. Furthermore, among the monomers constituting the styrene-based resin, examples of monomers other than the styrene-based monomers include (meth)acrylic acid ester-based monomers, maleimide-based monomers such as maleimide, N-methylmaleimide, and N-phenylmaleimide, α,β-unsaturated carboxylic acids and their anhydrides such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, phthalic acid, and itaconic acid, and rubbers such as butadiene.
[0029] The polystyrene resin used in this embodiment may contain a rubber-reinforced polystyrene resin. Specific examples of the rubber-reinforced polystyrene resin include acrylonitrile-styrene copolymer (AS resin), high impact polystyrene resin (HIPS), acrylonitrile-butadiene-styrene copolymer (ABS resin), acrylonitrile-acrylic rubber-styrene copolymer (AAS resin), acrylonitrile-styrene-acrylic rubber copolymer (ASA resin), acrylonitrile-ethylene propylene rubber-styrene copolymer (AES resin), and styrene-IPN type rubber copolymer.
[0030] It is also preferable that the polystyrene-based resin used in this embodiment is partly a styrene-maleic acid polymer (preferably a styrene-maleic anhydride polymer). The styrene-maleic acid polymer acts as a compatibilizer between the polybutylene terephthalate resin and the polystyrene resin and / or the rubber-reinforced polystyrene resin. As a result, the strength of the resulting molded product can be increased.
[0031] In this embodiment, the polystyrene resin preferably includes at least one selected from polystyrene resin (GPPS), acrylonitrile-styrene copolymer (AS resin), high impact polystyrene resin (HIPS), acrylonitrile-butadiene-styrene copolymer (ABS resin), acrylonitrile-acrylic rubber-styrene copolymer (AAS resin), acrylonitrile-styrene-acrylic rubber copolymer (ASA resin), and acrylonitrile-ethylene propylene rubber-styrene copolymer (AES resin), and more preferably includes high impact polystyrene resin (HIPS). Also, from the viewpoint of heat resistance, polystyrene resin (GPPS) and acrylonitrile-styrene copolymer (AS resin) are more preferable.
[0032] The polystyrene resin used in the present embodiment may contain recycled products. Examples of recycled polystyrene resin include leftover or rejected molded products, and products obtained through material recycling in which recovered used polystyrene resin molded products are crushed, washed, and reused, as well as products obtained through chemical recycling (chemical decomposition methods).
[0033] <Blend ratio of polyalkylene terephthalate resin and styrene resin> In the resin composition of the present embodiment, the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) and the styrene-based resin are contained in a ratio of 10 to 90 parts by mass of the polyalkylene terephthalate resin and 90 to 10 parts by mass of the styrene-based resin in a total of 100 parts by mass. Furthermore, the styrene-based resin is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 40 parts by mass or more, even more preferably 50 parts by mass or more, even more preferably more than 50 parts by mass, even more preferably 55 parts by mass or more, and especially more preferably 57 parts by mass or more in a total of 100 parts by mass of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) and the styrene-based resin. By making it equal to or more than the lower limit, the low warpage tends to be further improved. The upper limit of the content of the styrene resin is 90 parts by mass or less, preferably 80 parts by mass or less, more preferably 75 parts by mass or less, even more preferably 70 parts by mass or less, and even more preferably 65 parts by mass or less, relative to 100 parts by mass in total of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) and the styrene resin. By keeping the content below the upper limit, heat resistance tends to be further improved.
[0034] The total content of the polyalkylene terephthalate resin and the styrene-based resin in the resin composition of this embodiment is preferably 35% by mass or more, more preferably 40% by mass or more, and even more preferably 45% by mass or more, in 100% by mass of the resin composition. By making it equal to or more than the lower limit, the fluidity of the resin tends to be further improved. In addition, the total content of the polyalkylene terephthalate resin and the styrene-based resin in the resin composition of this embodiment is preferably 65% by mass or less, more preferably 60% by mass or less, even more preferably 55% by mass or less, and even more preferably 50% by mass or less, in 100% by mass of the resin composition. By making it equal to or less than the upper limit, the mechanical strength tends to be further improved. In addition, the weight of the obtained molded product can be reduced.
[0035] The resin composition of the present embodiment may contain only one type of polyalkylene terephthalate resin and one type of styrene-based resin, or may contain two or more types of polyalkylene terephthalate resin and one or more types of styrene-based resin.
[0036] <Flame retardants> The resin composition of the present embodiment contains a flame retardant. By containing the flame retardant, flame retardancy can be achieved. Examples of flame retardants include halogen-based flame retardants, phosphorus-based flame retardants (metal phosphinate, melamine polyphosphate, etc.), nitrogen-based flame retardants (melamine cyanurate, etc.), and metal hydroxides (magnesium hydroxide, etc.). Phosphorus-based flame retardants and halogen-based flame retardants are preferred, and halogen-based flame retardants are more preferred. As phosphorus-based flame retardants, metal phosphinate is more preferred. As halogen-based flame retardants, bromine-based flame retardants are more preferred.
[0037] When a brominated flame retardant is used as the flame retardant, the type thereof is not particularly limited, but brominated phthalimide, brominated poly(meth)acrylate, brominated polycarbonate, brominated epoxy, and brominated polystyrene are preferred, brominated phthalimide, brominated polycarbonate, and brominated epoxy are more preferred, brominated phthalimide and brominated epoxy are even more preferred, and brominated phthalimide is even more preferred.
[0038] The brominated phthalimide is preferably one represented by the formula (1). [ka] (In formula (1), D represents an alkylene group, an arylene group, -S(=O)2-, -C(=O)-, and a group formed by combining two or more of -O-. i is an integer of 1 to 4.)
[0039] In formula (1), D represents a group consisting of a combination of two or more of an alkylene group, an arylene group, -S(=O)2-, -C(=O)-, and -O-. A group consisting of a combination of an alkylene group or an arylene group and at least one of -S(=O)2-, -C(=O)-, and -O- is preferable, a group consisting of a combination of an alkylene group or an arylene group and one of -S(=O)2-, -C(=O)-, and -O- is more preferable, and an alkylene group is further preferable. The group consisting of a combination of an alkylene group and -O- is intended to include, for example, a combination of two alkylene groups and one -O- (the same applies to other combinations). The alkylene group represented by D is preferably an alkylene group having 1 to 6 carbon atoms, more preferably a methylene group, an ethylene group, a propylene group, or a butylene group. The arylene group is preferably a phenylene group. "i" is an integer of 1 to 4, and is preferably 4.
[0040] Examples of the brominated phthalimide represented by formula (1) include N,N'-(bistetrabromophthalimide)ethane, N,N'-(bistetrabromophthalimide)propane, N,N'-(bistetrabromophthalimide)butane, N,N'-(bistetrabromophthalimide)diethyl ether, N,N'-(bistetrabromophthalimide)dipropyl ether, N,N'-(bistetrabromophthalimide)dibutyl ether, N,N'-(bistetrabromophthalimide)diphenyl sulfone, N,N'-(bistetrabromophthalimide)diphenyl ketone, and N,N'-(bistetrabromophthalimide)diphenyl ether.
[0041] The brominated phthalimide represented by formula (1) is preferably a brominated phthalimide represented by formula (2). [ka] (In formula (2), i is an integer of 1 to 4.) "i" is an integer of 1 to 4, and is preferably 4.
[0042] The brominated poly(meth)acrylate is preferably a polymer obtained by polymerizing a bromine atom-containing benzyl (meth)acrylate alone, copolymerizing two or more kinds of the bromine atom-containing benzyl (meth)acrylate, or copolymerizing the bromine atom with another vinyl monomer, and the bromine atoms are added to a benzene ring with 1 to 5 bromine atoms, preferably 4 to 5 bromine atoms, added per benzene ring.
[0043] Examples of the benzyl acrylate containing a bromine atom include pentabromobenzyl acrylate, tetrabromobenzyl acrylate, tribromobenzyl acrylate, and mixtures thereof. Examples of the benzyl methacrylate containing a bromine atom include methacrylates corresponding to the above-mentioned acrylates.
[0044] Specific examples of other vinyl monomers that can be copolymerized with the bromine atom-containing benzyl (meth)acrylate include acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, and benzyl acrylate; methacrylic acid, methyl methacrylate, ethyl methacrylate, butyl methacrylate, and benzyl methacrylate; unsaturated carboxylic acids or anhydrides thereof, such as styrene, acrylonitrile, fumaric acid, and maleic acid; vinyl acetate, and vinyl chloride.
[0045] These are usually used in an equimolar amount or less, particularly preferably 0.5 times the molar amount or less, relative to the bromine atom-containing benzyl (meth)acrylate.
[0046] Furthermore, examples of vinyl monomers that can be used include xylylene diacrylate, xylylene dimethacrylate, tetrabromo xylylene diacrylate, tetrabromo xylylene dimethacrylate, butadiene, isoprene, and divinylbenzene. These can usually be used in an amount of 0.5 or less by mole relative to the bromine atom-containing benzyl acrylate or benzyl methacrylate.
[0047] The brominated poly(meth)acrylate is preferably a polymer obtained by polymerizing a bromine atom-containing (meth)acrylate monomer, particularly benzyl (meth)acrylate, alone or by copolymerizing two or more kinds of the monomers, or by copolymerizing the monomers with other vinyl monomers. The bromine atoms are added to the benzene ring, and the number of added bromine atoms is preferably 1 to 5, more preferably 4 to 5, per benzene ring.
[0048] As the brominated poly(meth)acrylate, pentabromobenzyl poly(meth)acrylate is preferred due to its high bromine content.
[0049] The molecular weight of the brominated poly(meth)acrylate is arbitrary and may be appropriately selected and determined, but the weight average molecular weight (Mw) is preferably 3,000 or more, more preferably 10,000 or more, even more preferably 15,000 or more, even more preferably 20,000 or more, and even more preferably 25,000 or more. By making it equal to or greater than the lower limit, a molded product having higher mechanical strength tends to be obtained. In addition, the upper limit of the weight average molecular weight (Mw) is preferably equal to or less than 100,000, more preferably equal to or less than 80,000, even more preferably equal to or less than 60,000, even more preferably equal to or less than 50,000, and even more preferably equal to or less than 35,000. By making it equal to or less than the upper limit, the flowability of the resin composition tends to be further improved.
[0050] The brominated polycarbonate preferably has a free bromine content of 0.05% by mass or more, and preferably 0.20% by mass or less. By setting the content within such a range, the heat resistance stability of the resin composition tends to be further improved. The brominated polycarbonate also preferably has a chlorine atom content of 0.001% by mass or more, and preferably 0.20% by mass or less. By setting the content within such a range, the mold corrosion resistance during molding tends to be further improved. Specifically, the brominated polycarbonate is preferably a brominated polycarbonate obtained from, for example, brominated bisphenol A, particularly tetrabromobisphenol A. Examples of the terminal structure include a phenyl group, a 4-t-butylphenyl group, and a 2,4,6-tribromophenyl group, and in particular, one having a 2,4,6-tribromophenyl group in the terminal group structure is preferred.
[0051] The average number of carbonate constituent units in the brominated polycarbonate may be appropriately selected and determined, but is preferably 2-30, more preferably 3-15, and even more preferably 3-10.
[0052] The molecular weight of the brominated polycarbonate is optional and may be appropriately selected and determined, but it is preferably from 1,000 to 20,000, more preferably from 2,000 to 10,000, in terms of viscosity average molecular weight.
[0053] The brominated polycarbonate obtained from the above brominated bisphenol A can be obtained, for example, by a conventional method of reacting brominated bisphenol with phosgene. The end-capping agent includes an aromatic monohydroxy compound, which may be substituted with a halogen or an organic group.
[0054] Specific preferred examples of the brominated epoxy include bisphenol A type brominated epoxy compounds, such as tetrabromobisphenol A epoxy compounds and glycidyl brominated bisphenol A epoxy compounds.
[0055] The molecular weight of the brominated epoxy compound is arbitrary and may be appropriately selected and determined, but the weight average molecular weight (Mw) is preferably 3,000 or more, more preferably 10,000 or more, even more preferably 13,000 or more, even more preferably 15,000 or more, and even more preferably 18,000 or more. By making it equal to or more than the lower limit, a molded product having higher mechanical strength tends to be obtained. In addition, the upper limit of the weight average molecular weight (Mw) is preferably 100,000 or less, more preferably 80,000 or less, even more preferably 78,000 or less, even more preferably 75,000 or less, even more preferably 70,000 or less, and may be 50,000 or less, 30,000 or less, or 25,000 or less. By making it equal to or less than the upper limit, the flowability of the resin composition tends to be further improved. The brominated epoxy compound preferably has an epoxy equivalent of 3,000 to 40,000 g / eq, more preferably 4,000 to 35,000 g / eq, and particularly preferably 10,000 to 30,000 g / eq.
[0056] In addition, a brominated epoxy oligomer can be used in combination as the brominated epoxy. In this case, for example, by using an oligomer having Mw of 5,000 or less at a ratio of about 50 mass% or less, the flame retardancy, releasability, and flowability can be appropriately adjusted. The bromine atom content in the brominated epoxy compound is arbitrary, but in order to impart sufficient flame retardancy, it is usually 10 mass% or more, preferably 20 mass% or more, and particularly preferably 30 mass% or more, with the upper limit being 60 mass%, and preferably 55 mass% or less.
[0057] The brominated polystyrene preferably includes a brominated polystyrene containing a constitutional unit represented by the formula (3). [ka] (In formula (3), t is an integer of 1 to 5, and n is the number of constitutional units.)
[0058] Brominated polystyrene may be produced by brominating polystyrene or by polymerizing brominated styrene monomer, but the polymerized brominated styrene has a smaller amount of free bromine (atoms), and is therefore preferred. In formula (3), the CH group to which the brominated benzene is bonded may be substituted with a methyl group. Brominated polystyrene may also be a copolymer in which other vinyl monomers are copolymerized. Examples of the vinyl monomer in this case include styrene, α-methylstyrene, (meth)acrylonitrile, (meth)methyl acrylate, butadiene, and vinyl acetate. Brominated polystyrene may be used alone or as a mixture of two or more types with different structures, and may contain units derived from styrene monomers with different bromine numbers in a single molecular chain.
[0059] Specific examples of brominated polystyrene include poly(4-bromostyrene), poly(2-bromostyrene), poly(3-bromostyrene), poly(2,4-dibromostyrene), poly(2,6-dibromostyrene), poly(2,5-dibromostyrene), poly(3,5-dibromostyrene), poly(2,4,6-tribromostyrene), poly(2,4,5-tribromostyrene), poly(2,3,5-tribromostyrene), and poly(4-bromo-α-methylstyrene). Examples of suitable styrene copolymers include poly(2,4-dibromostyrene), poly(2,5-dibromo-α-methylstyrene), poly(2,4,6-tribromo-α-methylstyrene) and poly(2,4,5-tribromo-α-methylstyrene), of which poly(2,4,6-tribromostyrene), poly(2,4,5-tribromostyrene) and polydibromostyrene and polytribromostyrene containing an average of 2 to 3 bromine groups in the benzene ring are particularly preferred.
[0060] The number n (average degree of polymerization) of the constituent units in the formula (3) of the brominated polystyrene is preferably 30 to 1,500, more preferably 150 to 1,000, and particularly preferably 300 to 800. If the average degree of polymerization is less than 30, blooming is likely to occur, while if it exceeds 1,500, poor dispersion is likely to occur and mechanical properties are likely to deteriorate. The weight-average molecular weight (Mw) of the brominated polystyrene is preferably 5,000 to 500,000, more preferably 10,000 to 500,000, even more preferably 10,000 to 300,000, even more preferably 10,000 to 100,000, and even more preferably 10,000 to 70,000. In particular, in the case of the above-mentioned brominated polystyrene, the weight average molecular weight (Mw) is preferably 50,000 to 70,000, and in the case of brominated polystyrene produced by a polymerization method, the weight average molecular weight (Mw) is preferably about 10,000 to 30,000.
[0061] The bromine concentration in the bromine-based flame retardant is preferably 45% by mass or more, more preferably 48% by mass or more, even more preferably 50% by mass or more, even more preferably 55% by mass or more, and may be 60% by mass or more. By setting the bromine concentration at or above the lower limit, the flame retardancy of the molded article tends to be effectively improved. The upper limit of the bromine concentration is preferably 75% by mass or less, more preferably 73% by mass or less, even more preferably 71% by mass or less, and may be 69% by mass or less.
[0062] When a metal phosphinate is used as a flame retardant, the type is not particularly limited, but it is preferable that the metal phosphinate has an anion portion represented by formula (4) or formula (5) and a metal ion of the cation portion is any one of calcium, magnesium, aluminum, and zinc.
[0063] [ka] (In the formula, R 1 and R 2each independently represents an alkyl group having 1 to 6 carbon atoms or an aryl group which may have a substituent; R 1 may be the same or different, R 3 represents an alkylene group having 2 to 10 carbon atoms, an arylene group which may have a substituent, or a group consisting of a combination thereof; R 3 may be the same or different, and n represents an integer of 0 to 2.) The aryl group which may have a substituent is preferably a phenyl group which may have a substituent. When it has a substituent, it is preferably an alkyl group having 1 to 3 carbon atoms. It is also preferably unsubstituted. The arylene group which may have a substituent is preferably a phenylene group which may have a substituent. The arylene group which may have a substituent is preferably unsubstituted or has an alkyl group having 1 to 3 carbon atoms (preferably a methyl group) as a substituent. In this embodiment, a metal phosphinate represented by formula (5) is preferred. Also, in this embodiment, aluminum phosphinate is preferred.
[0064] Specific examples of the metal phosphinate include calcium dimethylphosphinate, magnesium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, magnesium ethylmethylphosphinate, aluminum ethylmethylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, magnesium diethylphosphinate, aluminum diethylphosphinate, zinc diethylphosphinate, calcium methyl-n-propylphosphinate, magnesium methyl-n-propylphosphinate, aluminum methyl-n-propylphosphinate, zinc methyl-n-propylphosphinate, and calcium methanedi(methylphosphinate). Examples of such compounds include magnesium methane di(methylphosphinate), aluminum methane bis(methylphosphinate), zinc methane bis(methylphosphinate), calcium benzene-1,4-bis(methylphosphinate), magnesium benzene-1,4-bis(methylphosphinate), aluminum benzene-1,4-bis(methylphosphinate), zinc benzene-1,4-bis(methylphosphinate), calcium methylphenylphosphinate, magnesium methylphenylphosphinate, aluminum methylphenylphosphinate, zinc methylphenylphosphinate, calcium diphenylphosphinate, magnesium diphenylphosphinate, aluminum diphenylphosphinate, and zinc diphenylphosphinate. For details about the metal phosphinate, reference can be made to paragraphs 0052 to 0058 of WO 2010 / 010669, the contents of which are incorporated herein by reference.
[0065] The content of the flame retardant (preferably a bromine-based flame retardant) in the resin composition of this embodiment is 0.5 parts by mass or more, preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, even more preferably 7 parts by mass or more, even more preferably 10 parts by mass or more, even more preferably 14 parts by mass or more, and particularly more preferably 16 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the styrene-based resin. By setting the content to the lower limit or more, the flame retardancy of the obtained molded product tends to be further improved. The upper limit of the content of the flame retardant is 45 parts by mass or less, preferably 40 parts by mass or less, more preferably 35 parts by mass or less, even more preferably 30 parts by mass or less, even more preferably 25 parts by mass or less, even more preferably 22 parts by mass or less, and even more preferably 20 parts by mass or less, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the styrene-based resin. By setting the content to be equal to or less than the upper limit, the decrease in mechanical strength of the obtained molded article can be more effectively suppressed. The resin composition of the present embodiment may contain only one type of flame retardant, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0066] <Polyolefin wax> The resin composition of the present embodiment contains a polyolefin wax. By containing the polyolefin wax, the mold releasability of the resulting resin composition can be improved. Polyolefin waxes are homopolymers or copolymers of olefins. Examples of polyolefin wax include polyethylene wax, polypropylene wax, and polyethylene propylene wax, with polyethylene wax being preferred. The polyolefin wax may be unmodified or modified. Examples of modified polyolefin wax include vinyl ester modified polyolefin wax, acid modified polyolefin wax, and oxidized polyolefin wax, with oxidized polyolefin wax being preferred. Oxidized polyolefin wax has excellent compatibility with polyalkylene terephthalate resins, and can effectively suppress mold deposits in the resulting resin composition.
[0067] The polyethylene wax may be made of an ethylene homopolymer or an ethylene-α-olefin copolymer. Examples of the α-olefin as the ethylene copolymer include α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, isobutylene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene, 1-octadecene, and 4-methyl-1-pentene. The content of ethylene units in the ethylene-α-olefin copolymer wax is preferably more than 50 mol%, and is preferably 60 to 100 mol%. The polyethylene wax may be unmodified or modified. Examples of unmodified polyethylene waxes include Licowax (registered trademark) PE520, PE130, and PE190; Licocene (registered trademark) PE3101TP, PE4201, and PE5301; and Ceridust (registered trademark) 3620 and 3610, all of which are manufactured by Clariant Chemicals.
[0068] The polypropylene wax may be made of a propylene homopolymer or a propylene-α-olefin copolymer. Examples of the α-olefin as the propylene copolymer include α-olefins having 3 to 20 carbon atoms, such as ethylene, 1-butene, isobutylene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene, 1-octadecene, and 4-methyl-1-pentene. The content of the propylene unit in the propylene-α-olefin copolymer wax is preferably more than 50 mol%, and is preferably 60 to 100 mol%. The polypropylene wax may be unmodified or modified. Examples of unmodified polypropylene waxes include Licocene (registered trademark) PP6102, PP6502, PP7502, PP1302, PP1502, PP1602, PP2602, and PP3602, all manufactured by Clariant Chemicals; and Ceridust (registered trademark) 6050M.
[0069] The vinyl ester modified polyolefin wax can be obtained by copolymerizing a monomer constituting the corresponding unmodified polyolefin wax with a vinyl ester such as vinyl acetate, vinyl propionate, etc. Examples of the vinyl acetate modified polyethylene wax include Licowax (registered trademark) 371FP manufactured by Clariant Chemicals.
[0070] The acid-modified polyolefin wax can be obtained by acid-modifying the corresponding unmodified polyolefin wax with an unsaturated carboxylic acid or its acid anhydride. Specific examples of the unsaturated carboxylic acid or its acid anhydride include maleic acid, fumaric acid, itaconic acid, acrylic acid, methacrylic acid, cis-4-cyclohexene-1,2-dicarboxylic acid, maleic anhydride, itaconic anhydride, cis-4-cyclohexene-1,2-dicarboxylic anhydride, etc., with maleic anhydride being preferred. Derivatives such as acid amides and acid esters can also be used instead of unsaturated carboxylic acid anhydrides. Examples of maleic anhydride-modified polyethylene wax include Licocene (registered trademark) PE MA 4221 and PE MA 4351 manufactured by Clariant Chemicals. Examples of maleic anhydride-modified polypropylene wax include Licocene (registered trademark) PP MA 1332, PP MA 6252, PP MA 6452, and PP MA 7452 manufactured by Clariant Chemicals.
[0071] The oxidized polyolefin wax can be obtained by oxidizing the corresponding unmodified polyolefin wax. Examples of the oxidized polyethylene wax include Licowax (registered trademark) PED521, PED522, and PED121 manufactured by Clariant Chemicals; Ceridust (registered trademark) 3715, and the like. In addition to the above, commercially available polyolefin waxes can be found in paragraph 0028 of JP-A-2022-140470, the contents of which are incorporated herein by reference.
[0072] The weight average molecular weight of the polyolefin wax is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, even more preferably 2,000 or more, and even more preferably 2,500 or more. By making it equal to or greater than the lower limit, the glowing time tends to be further shortened. In addition, the weight average molecular weight of the polyolefin wax is preferably 30,000 or less, more preferably 20,000 or less, even more preferably 15,000 or less, and even more preferably 10,000 or less. By making it equal to or less than the upper limit, the flowability of the resin composition during molding tends to be further improved. The weight average molecular weight can be measured by GPC (gel permeation chromatography) using a Tosoh HLC-8320GPC EcoSEC, tetrahydrofuran as the solvent, three Shodex KF-G, KF-805L, and a KF-800D as columns, at a column temperature of 40°C and a flow rate of 1.2 mL / min, and is measured as a polystyrene equivalent value detected with a detector (UV-8320) at a detection wavelength of 254 nm. In the case where the resin composition in the present embodiment contains two or more types of polyolefin waxes, the weight average molecular weight is the weight average molecular weight of the mixture.
[0073] The dropping point of the polyolefin wax is preferably 165°C or lower, more preferably 160°C or lower, even more preferably 155°C or lower, even more preferably 150°C or lower, even more preferably 145°C or lower, even more preferably 140°C or lower, even more preferably 135°C or lower, particularly more preferably 130°C or lower, and preferably 80°C or higher, more preferably 85°C or higher, even more preferably 85°C or higher, even more preferably 90°C or higher, and even more preferably 95°C or higher. The dropping point is determined by heating a polyolefin wax until it changes from a solid to a liquid state and the temperature at which the first drop of molten material falls from a standard cup having an opening of 2.8 mm.
[0074] The content of the polyolefin wax in the resin composition of the present embodiment is 0.01 parts by mass or more, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.5 parts by mass or more, and even more preferably 0.8 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the styrene-based resin. By making it equal to or more than the lower limit, there is a tendency that the deterioration of the mold releasability can be more effectively suppressed. In addition, the upper limit of the content of the polyolefin wax is 10 parts by mass or less, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 2 parts by mass or less, even more preferably 1.5 parts by mass or less, and even more preferably 1.2 parts by mass or less, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the styrene-based resin. By making it equal to or less than the upper limit, there is a tendency that the deterioration of the heat resistance and the deterioration of the mechanical properties can be more effectively suppressed. The resin composition of the present embodiment may contain only one type of polyolefin wax, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0075] The resin composition of the present embodiment may or may not contain a release agent other than the polyolefin wax. The resin composition of the present embodiment may be configured to be substantially free of any release agent other than the polyolefin wax. Substantially free of any release agent other than the polyolefin wax means that the content of the release agent other than the polyolefin wax is less than 10% by mass of the content of the polyolefin wax, preferably less than 5% by mass, more preferably less than 3% by mass, and even more preferably less than 1% by mass. Examples of the release agent other than the polyolefin wax include montan acid ester wax, polyolefin wax, higher fatty acid, higher fatty acid amide, ester compound, ethylene bis stearamide, and the like.
[0076] <Compatibilizer> The resin composition of the present embodiment may contain a compatibilizer. The compatibilizer in the present embodiment functions as a compatibilizer for the polyalkylene terephthalate resin and the styrene-based resin. However, when other components such as the above-mentioned styrene-maleic acid polymer function as a compatibilizer, the compatibilizer is not necessarily required. In this embodiment, the compatibilizer is preferably a polycarbonate resin.
[0077] Polycarbonate resins are homopolymers or copolymers, which may be branched, obtained by reacting a dihydroxy compound or a small amount of a polyhydroxy compound with phosgene or a carbonic acid diester. The method for producing the polycarbonate resin is not particularly limited, and polycarbonate resins produced by the conventionally known phosgene method (interfacial polymerization method) or melting method (ester exchange method) can be used.
[0078] The dihydroxy compound as the raw material is preferably an aromatic dihydroxy compound, more preferably bisphenol, further preferably 2,2-bis(4-hydroxyphenyl)propane (=bisphenol A), tetramethylbisphenol A, bis(4-hydroxyphenyl)-p-diisopropylbenzene, hydroquinone, resorcinol, 4,4-dihydroxydiphenyl, etc., and even more preferably bisphenol A. Also usable are compounds in which one or more tetraalkylphosphonium sulfonates are bonded to the above aromatic dihydroxy compounds.
[0079] As the polycarbonate resin, among the above, aromatic polycarbonate resin (bisphenol A type polycarbonate resin) derived from 2,2-bis(4-hydroxyphenyl)propane, or aromatic polycarbonate copolymer derived from 2,2-bis(4-hydroxyphenyl)propane and other aromatic dihydroxy compounds is preferable. In addition, it may be a copolymer mainly composed of aromatic polycarbonate resin, such as a copolymer with a polymer or oligomer having a siloxane structure. Furthermore, two or more of the above polycarbonate resins may be mixed and used.
[0080] In order to adjust the molecular weight of the polycarbonate resin, a monovalent aromatic hydroxy compound may be used, such as m- and p-methylphenol, m- and p-propylphenol, p-tert-butylphenol, and p-long-chain alkyl-substituted phenol.
[0081] The viscosity average molecular weight (Mv) of the polycarbonate resin is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 13,000 or more. By using a polycarbonate resin having a viscosity average molecular weight (Mv) of 5,000 or more, the mechanical strength of the obtained resin composition tends to be further improved. In addition, the viscosity average molecular weight (Mv) of the polycarbonate resin is preferably 60,000 or less, more preferably 40,000 or less, even more preferably 30,000 or less, even more preferably 25,000 or less, and may be 20,000 or less. By using a polycarbonate resin having a viscosity average molecular weight (Mv) of 60,000 or less, the flowability of the resin composition tends to be improved and the moldability tends to be improved. When two or more types of polycarbonate resins are contained, it is preferable that the mixture satisfies the above range.
[0082] In this embodiment, the viscosity average molecular weight (Mv) of the polycarbonate resin is a value calculated from the intrinsic viscosity ([η]) of a methylene chloride solution of the polycarbonate resin measured at 20° C. using an Ubbelohde viscometer, and the intrinsic viscosity calculated from the following Schnell viscosity formula. [η]=1.23×10 -4 Mv 0.83
[0083] The melt volume rate (MVR) of polycarbonate resin, measured in accordance with JIS K7210 (temperature 300°C, load 1.2 kgf), is usually 1 cm 3 / 10 minutes or more, 3cm 3 By setting the MVR to the above lower limit or more, the flowability of the resulting resin composition or molded article tends to be improved. 3 / 10 minutes or less, and even 50 cm 3 / 10 minutes or less is preferable, and more preferably, 30 cm 3 / 10 minutes or less, 20cm 3 / 10 minutes or less, 10cm 3 / 10 minutes or less is acceptable. The melt flow rate (MFR) of the polycarbonate resin measured in accordance with JIS K7210 (temperature 300°C, load 1.2 kgf) is usually 1g / 10min or more, preferably 3g / 10min or more, and more preferably 5g / 10min or more. By setting it to the lower limit or more, the fluidity of the obtained resin composition or molded product tends to be further improved. The upper limit of the MFR is, for example, 100g / 10min or less, and preferably 50g / 10min or less, and may be 30g / 10min or less, 20g / 10min or less, or 10g / 10min or less.
[0084] The method for producing the polycarbonate resin is not particularly limited, and polycarbonate resins produced by either the phosgene method (interfacial polymerization method) or the melting method (ester exchange method) can be used. In addition, polycarbonate resins produced by the melting method and then subjected to post-treatment to adjust the amount of OH groups at the terminals are also preferred.
[0085] The polycarbonate resin may be a recycled product. In the present embodiment, even if a recycled product is used as the polycarbonate resin, the same performance as that of a virgin polycarbonate resin can be achieved.
[0086] The content of the compatibilizer is preferably 1 part by mass or more, more preferably 5 parts by mass or more, even more preferably 8 parts by mass or more, and may be 10 parts by mass or more, relative to 100 parts by mass of the total of the polybutylene terephthalate resin and the polystyrene resin. By making it equal to or more than the lower limit, the compatibility with the polybutylene terephthalate resin and the polystyrene resin is improved, and the mechanical strength of the obtained molded article tends to be improved. The content of the compatibilizer is preferably 35 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 25 parts by mass or less, even more preferably 20 parts by mass or less, and may be 15 parts by mass or less, relative to 100 parts by mass of the total of the polybutylene terephthalate resin and the polystyrene resin. By making it equal to or less than the upper limit, the heat resistance of the obtained molded article tends to be maintained at a high level.
[0087] <Reinforced filler> The resin composition of the present embodiment may contain a reinforcing filler. The reinforcing filler has the effect of improving the mechanical properties of the resin composition obtained by blending it with the resin, and a wide variety of commonly used reinforcing fillers for plastics can be used. The shape of the reinforcing filler that can be used in the present embodiment is not particularly limited, and may be any of fibers, fillers, beads, etc., but fibers are preferred.
[0088] When the reinforcing filler is a fiber, it may be a short fiber or a long fiber. Raw materials for the reinforcing filler include inorganic substances such as glass, carbon (carbon fiber, etc.), alumina, boron, ceramics, and metals (steel, etc.), and organic substances such as plants (including kenaf, bamboo, etc.), aramid, polyoxymethylene, aromatic polyamide, polyparaphenylene benzobisoxazole, and ultra-high molecular weight polyethylene, with glass being preferred.
[0089] The resin composition in this embodiment preferably contains glass fibers as a reinforcing filler. The glass fibers are selected from glass compositions such as A-glass, C-glass, E-glass, R-glass, D-glass, M-glass, and S-glass, with E-glass (alkali-free glass) being particularly preferred. Glass fiber refers to a fibrous material whose cross section cut perpendicularly to the length direction has a perfect circle or polygonal shape. The number average fiber diameter of the single fiber of the glass fiber is usually 1 to 25 μm, preferably 5 to 17 μm. By making the number average fiber diameter 1 μm or more, the moldability of the resin composition tends to be improved. By making the number average fiber diameter 25 μm or less, the appearance of the obtained structure tends to be improved, and the reinforcing effect also tends to be improved. The glass fiber may be a single fiber or a plurality of single fibers twisted together. The form of the glass fiber may be any of glass rovings obtained by continuously winding single fibers or multiple twisted fibers, chopped strands cut to a length of 1 to 10 mm (i.e., glass fibers having a number average fiber length of 1 to 10 mm), milled fibers pulverized to a length of about 10 to 500 μm (i.e., glass fibers having a number average fiber length of 10 to 500 μm), etc., but chopped strands cut to a length of 1 to 10 mm are preferred. Glass fibers of different forms can also be used in combination. Glass fibers having an irregular cross-sectional shape are also preferred. The irregular cross-sectional shape has an aspect ratio, which is the long axis / short axis ratio of a cross section perpendicular to the longitudinal direction of the fiber, of, for example, 1.5 to 10, preferably 2.5 to 10, more preferably 2.5 to 8, and even more preferably 2.5 to 5.
[0090] The glass fiber may be surface-treated with, for example, a silane-based compound, an epoxy-based compound, a urethane-based compound, or the like, or may be oxidized, in order to improve its affinity with the resin component, as long as the properties of the resin composition in this embodiment are not significantly impaired.
[0091] The resin composition in this embodiment preferably contains 10 parts by mass or more of a reinforcing filler (preferably glass fiber) relative to 100 parts by mass of the total of the polybutylene terephthalate resin and the polystyrene-based resin, more preferably 20 parts by mass or more, even more preferably 35 parts by mass or more, even more preferably 45 parts by mass or more, even more preferably 55 parts by mass or more, and may be 60 parts by mass or more. By making it equal to or more than the lower limit, the mechanical strength of the obtained molded article tends to be further increased. In addition, the content of the reinforcing filler (preferably glass fiber) is preferably 300 parts by mass or less, more preferably 270 parts by mass or less, even more preferably 250 parts by mass or less, even more preferably 200 parts by mass or less, even more preferably 170 parts by mass or less, even more preferably 150 parts by mass or less, even more preferably 100 parts by mass or less, and may be 80 parts by mass or less, relative to 100 parts by mass of the total of the polybutylene terephthalate resin and the polystyrene-based resin. By making it equal to or less than the upper limit, the appearance of the obtained molded article tends to be further improved.
[0092] The content of the reinforcing filler (preferably glass fiber) in the resin composition in this embodiment is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and even more preferably 25% by mass or more, in 100% by mass of the resin composition. The content of the reinforcing filler (preferably glass fiber) in the resin composition is more preferably 60% by mass or less, even more preferably 55% by mass or less, even more preferably 45% by mass or less, even more preferably 40% by mass or less, and even more preferably 35% by mass or less. By making it equal to or more than the lower limit, the mechanical strength tends to be further increased. Also, by making it equal to or less than the upper limit, the appearance of the obtained molded product tends to be further improved. The resin composition in this embodiment may contain only one type of reinforcing filler (preferably glass fiber), or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0093] <Other ingredients> The resin composition of the present embodiment is substantially free of fluoropolymer. Fluoropolymer includes polytetrafluoroethylene (PTFE), which is also known as an anti-dripping agent. In the resin composition of the present embodiment, substantially free of fluoropolymer means that the content of fluoropolymer contained in the resin composition is preferably less than 0.1 mass%, more preferably less than 0.01 mass%, even more preferably less than 0.001 mass%, and most preferably free of fluoropolymer, based on 100 mass% of the resin composition. Furthermore, the content of fluorine atoms in the resin composition of this embodiment is preferably 2000 ppb by mass or less, more preferably 1500 ppb by mass or less, even more preferably 1000 ppb by mass or less, still more preferably 800 ppb by mass or less, even more preferably 600 ppb by mass or less, even more preferably 500 ppb by mass or less, and most preferably no fluorine atoms are present, relative to 100 mass% of the resin composition.
[0094] The resin composition of the present embodiment may contain other components in addition to the above-mentioned components as necessary, as long as the desired physical properties are not significantly impaired. The other components may be contained alone or in any combination and ratio of two or more. Specific examples of resin additives include stabilizers (heat stabilizers, light stabilizers), flame retardant assistants, colorants (pigments, dyes), nucleating agents, reactive compounds, antistatic agents, antifogging agents, antiblocking agents, flow improvers, plasticizers, and dispersants. Other components that are blended as necessary into the resin composition of the present embodiment are preferably components that do not contain fluorine atoms. Here, "not containing fluorine atoms" means that they are not blended intentionally, and is intended to exclude components that are blended unintentionally, such as impurities. However, as described above, the content of fluorine atoms in the finally obtained resin composition is preferably 2000 ppb by mass or less relative to 100% by mass of the resin composition. The total amount of these other components is preferably 0 to 10 mass %, and more preferably 0 to 5 mass %, in 100 mass % of the resin composition. In the resin composition of the present embodiment, the total amount of the polybutylene terephthalate resin, the styrene-based resin, the flame retardant, the olefin wax, and any other components blended as required is 100 mass %. In the resin composition of this embodiment, the total of the polybutylene terephthalate resin, styrene-based resin, flame retardant, olefin wax, compatibilizer, stabilizer, flame retardant assistant, colorant, and reinforcing filler preferably accounts for 90 mass% or more of the resin composition, more preferably 95 mass% or more, and may even be 100 mass%.
[0095] <<Stabilizer>> The resin composition of the present embodiment may contain a stabilizer (a light stabilizer and / or a heat stabilizer). Examples of the stabilizer include hindered phenol compounds, hindered amine compounds, phosphorus compounds, and sulfur stabilizers, and hindered phenol compounds and phosphorus compounds are preferred. In this embodiment, it is also preferred to use a hindered phenol compound, a phosphorus compound, and a sulfur stabilizer in combination. By using three types of stabilizers in combination in this way, the thermal stability is further improved and tends to continue for a long period of time. As the stabilizer, specifically, the description in paragraphs 0067 to 0075 of JP 2021-063196 A, the description in paragraphs 0046 to 0057 of JP 2018-070722 A, the description in paragraphs 0030 to 0037 of JP 2019-056035 A, and the description in paragraphs 0066 to 0078 of WO 2017 / 038949 can be referred to, the contents of which are incorporated herein by reference.
[0096] The melting point of the stabilizer used in this embodiment is preferably 50 to 140°C.
[0097] When the resin composition of the present embodiment contains a stabilizer, the content is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the styrene-based resin. By making the content equal to or more than the lower limit, the effect of suppressing thermal deterioration and oxidative deterioration of the resin during melt kneading, molding, and use as a molded product tends to be improved. In addition, the upper limit of the content of the stabilizer is preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the styrene-based resin. By making the content equal to or less than the upper limit, adverse effects on appearance and physical properties due to aggregation of additives such as stabilizers can be effectively suppressed. The resin composition of the present embodiment may contain only one type of stabilizer, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0098] <<Flame retardant synergist>> The resin composition of the present embodiment may contain a flame retardant assistant. By containing the flame retardant assistant, the flame retardancy of the molded article can be further improved. The flame retardant assistant is particularly preferably used when a halogen-based flame retardant is contained. The flame retardant assistant used in the present embodiment is exemplified by antimony compounds, such as antimony trioxide (Sb2O3), antimony pentoxide (Sb2O5), and sodium antimonate. In particular, antimony oxide, and particularly antimony trioxide, is preferred from the viewpoint of impact resistance. When a flame retardant auxiliary is blended, it may be blended as a master batch. The content of the antimony compound in the master batch is preferably 30 to 90 mass%, more preferably 40 to 85 mass%, further preferably 50 to 85 mass%, even more preferably 60 to 85 mass%, and still more preferably 70 to 85 mass%. The resin used in the master batch is preferably a polyester resin, and more preferably a polybutylene terephthalate resin.
[0099] When the resin composition of the present embodiment contains a flame retardant auxiliary (for example, an antimony compound), the content is preferably 0.1 parts by mass or more, more preferably 1.0 parts by mass or more, even more preferably 2.0 parts by mass or more, and even more preferably 3.0 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the styrene-based resin. By making the content equal to or more than the lower limit, the flame retardancy tends to be more effectively exhibited. In addition, the upper limit of the content of the antimony compound is preferably 20.0 parts by mass or less, more preferably 15.0 parts by mass or less, and even more preferably 10.0 parts by mass or less, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the styrene-based resin. By making the content equal to or less than the upper limit, the mold release property and impact resistance of the obtained molded product tend to be improved. The resin composition of the present embodiment may contain only one type of flame retardant auxiliary, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0100] <<Coloring agent>> The resin composition of the present embodiment may contain a colorant (dye and / or pigment). The colorant may be either a dye or a pigment, with the pigment being preferred. The colorant may be either an organic colorant or an inorganic colorant, and may be either a chromatic colorant or an achromatic colorant. Examples of colorants include those described in paragraphs 0121 to 0123 of JP 2021-101020 A and paragraphs 0088 to 0090 of JP 2019-188393 A, the contents of which are incorporated herein by reference. The resin composition of the present embodiment preferably contains carbon black. The carbon black is not limited in type, raw material type, or production method, and any of furnace black, channel black, acetylene black, ketjen black, etc. can be used. Among them, furnace black is preferable. There is no particular limit to the number average particle size, but it is preferably about 5 to 60 nm.
[0101] DBP oil absorption of carbon black (unit: cm 3 / 100g) is 40~300cm 3 / 100g. The upper limit is preferably 300 cm 3 / 100g or less is preferable, and 200cm 3 / 100g or less is more preferable, and 150cm 3 More preferably, the weight is 100g or less. 3 The lower limit may be 40 cm / 100 g or less. 3 / 100g or more is preferable, 50cm 3 / 100g or more is preferable, 60cm 3 By keeping the value within the upper and lower limits, the appearance of the molded product tends to be improved. 3 / 100g) can be measured in accordance with JIS K6217. The number average particle size of carbon black is preferably 5 to 60 nm. The upper limit is preferably 60 nm or less, more preferably 40 nm or less, even more preferably 30 nm or less, and even more preferably 25 nm or less. The lower limit is preferably 10 nm or more, more preferably 13 nm or more, even more preferably 16 nm or more, and even more preferably 19 nm or more. By keeping the upper and lower limits, the appearance of the molded product tends to be improved. The number average particle size can be obtained by obtaining an aggregate enlarged image according to the procedure described in the ASTM D3849 standard (Standard Test Method for Carbon Black-Morphological Characterization by Electron Microscopy), measuring the particle sizes of 3,000 unit constituent particles from this aggregate image, and taking the arithmetic average.
[0102] Carbon black is mixed in advance with a thermoplastic resin, preferably a polyester resin such as polybutylene terephthalate resin, or a styrene-based resin, to prepare a master batch, which tends to increase the dispersibility of the carbon black and improve the appearance of the molded product. The concentration of carbon black in the master batch is preferably 10 to 40% by mass.
[0103] When the resin composition of the present embodiment contains a colorant (preferably carbon black), the content is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.1 parts by mass or more, and even more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the styrene-based resin. By making it equal to or more than the lower limit, the coloring effect is more effectively exhibited. In addition, the upper limit of the content of the colorant is preferably 4 parts by mass or less, more preferably 2 parts by mass or less, and may be 1 part by mass or less, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the styrene-based resin. By making it equal to or less than the upper limit, the mechanical strength of the obtained molded product tends to be further improved. The resin composition of the present embodiment may contain only one type of colorant, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0104] <Physical properties of resin composition> The resin composition of the present embodiment is preferably excellent in flame retardancy. For example, when the resin composition is molded into a test piece having a thickness of 1.6 mm and subjected to a UL-94 test, it is preferable that the composition satisfies V-0. In particular, when the resin composition is molded into a test piece having a thickness of 1.6 mm and subjected to a UL-94 test, it is preferable that the composition satisfies V-0 after being left at 70° C. for one week. The resin composition of the present embodiment preferably has a short glowing time. Specifically, when the resin composition is molded into a test piece having a thickness of 1.6 mm and subjected to a UL-94 test, the total glowing time after the second ignition for five test pieces is preferably 31 seconds or less. The lower limit is 0 seconds or more, but 1 second or more is practical. Flame retardancy is measured as described in the Examples section below.
[0105] <Method of producing resin composition> The resin composition of this embodiment can be produced by a conventional method for preparing a resin composition (e.g., pellets). Usually, the components and various additives added as desired are thoroughly mixed together and then melt-kneaded in a single-screw or twin-screw extruder. The resin composition of this embodiment can also be prepared without premixing the components, or by premixing only a portion of the components, feeding the mixture to an extruder using a feeder and melt-kneading it. A portion of the components, such as a colorant, may be melt-kneaded with a thermoplastic resin to prepare a master batch, and then the remaining components may be blended therewith and melt-kneaded. In this embodiment, it is preferable to melt-knead the polybutylene terephthalate resin, the styrene-based resin, the flame retardant, the olefin wax, and the components to be blended as necessary, but it is preferable that these components do not contain fluorine atoms. Here, not containing fluorine atoms means that they are not intentionally blended, and the purpose is to exclude components that are unintentionally blended, such as impurities. However, as described above, the content of fluorine atoms in the finally obtained resin composition is preferably 2000 ppb by mass or less relative to 100% by mass of the resin composition. The glass fibers are preferably fed from a side feeder midway through the cylinder of the extruder. The heating temperature during melt kneading can be appropriately selected from the range of 220 to 300°C. If the temperature is too high, decomposition gas is likely to be generated, which may cause opacity. Therefore, it is desirable to select a screw configuration that takes into consideration shear heat generation, etc. In order to suppress decomposition during kneading and molding in the subsequent process, it is desirable to use an antioxidant or heat stabilizer.
[0106] <Method of manufacturing molded products> The resin composition or pellets of the present embodiment are molded according to a known method. The manufacturing method of the molded product is not particularly limited, and any molding method generally used for resin compositions can be used. Examples of such molding methods include injection molding, ultra-high speed injection molding, injection compression molding, two-color molding, gas-assisted hollow molding, molding using a heat-insulating mold, molding using a rapid heating mold, foam molding (including supercritical fluid), insert molding, IMC (in-mold coating molding), extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, etc., and among these, injection molding is preferred. For details of the injection molding method, refer to paragraphs 0113 to 0116 of Japanese Patent No. 6183822, the contents of which are incorporated herein by reference. The mold temperature during molding such as injection molding is preferably 40 to 150°C.
[0107] <Application> The resin composition of the present embodiment is used as a molded product formed from the resin composition or pellets. The applications of the resin composition and pellets are not particularly limited, and they can be widely used indoors or outdoors as materials for electrical and electronic equipment, automobiles, housing, and materials for manufacturing parts in other industrial fields. The molded article of the present embodiment is also excellent in flame retardancy even when placed under high temperatures for a long period of time, and is therefore preferably used for outdoor applications. Examples of outdoor applications include outdoor use (installation) device parts such as the exterior of a power meter (also called a power meter or an electric meter). More specifically, examples include the cover, housing, and enclosure of a power meter.
[0108] Automotive materials include lamp housings, reflectors, bezels, extensions, connectors, ECU cases, housings for in-vehicle cameras and millimeter-wave radars, battery cases, and sensor housings. Examples of electric and electronic components include various housings, display devices such as computers, game consoles and televisions, printers, copy machines, scanners, fax machines, electronic organizers and PDAs, electronic desk calculators, electronic dictionaries, cameras, video cameras, mobile phones, battery packs, drives and readers for recording media, mice, numeric keypads, CD players, MD players, portable radio and audio players, housings, covers, keyboards, buttons, switch components, casings for power meters, battery cases, battery transport trays, relays, sensors, actuators, terminal switches, and grill cooking equipment parts. EXAMPLES
[0109] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.
[0110] 1.Raw materials The raw materials shown in Table 1 were used. [Table 1]
[0111] Example 1, Comparative Examples 1 to 3 <Compound> The components shown in Table 1 were mixed uniformly in a tumbler mixer in the ratios shown in Table 2 (each component in Table 2 is shown in parts by mass), with the exception of the glass fibers. The mixture obtained was fed to a twin-screw extruder ("TEX30α" manufactured by Japan Steel Works, Ltd.) from the main feed port. The cylinder temperature setting of the first kneading section was set to 260°C, and the glass fibers were fed from a side feeder. The resin composition was melt-kneaded under conditions of a cylinder temperature setting of 260°C after the addition of the glass fibers and a screw rotation speed of 200 rpm, and was quenched in a water tank and pelletized using a pelletizer to obtain pellets of the resin composition.
[0112] <Bending strength> The pellets obtained above were dried at 110°C for 5 hours, and then injection molded into 4 mm thick ISO test pieces using an injection molding machine (Japan Steel Works, Ltd., "J85AD") under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C. In accordance with ISO178, the flexural strength (unit: MPa) was measured at a temperature of 23°C using the above ISO tensile test pieces (4 mm thick).
[0113] <Flame retardancy> The resin composition pellets obtained above were dried at 110°C for 5 hours, and then injection molded into combustion test specimens (12.7 mm width x 127 mm length x 1.6 mm thickness) using an injection molding machine (Japan Steel Works, Ltd., "J-50AD") under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C. The obtained combustion test specimens were left to stand in an atmosphere of 70°C for one week, and then the flame retardancy was evaluated according to the Underwriters Laboratories Subject 94 (UL94) method. The glowing time after the second flame application was also measured. The total glowing time of the five pieces was evaluated as follows: A: 31 seconds or less B: More than 31 seconds but less than 36 seconds C: More than 36 seconds
[0114] <Mold releasability> The pellets obtained above were dried at 120°C for 5 hours, and then a box-shaped molded product with a thickness of 1.5 mmt and external dimensions of 30 x 50 x 30 mm depth was molded using an injection molding machine (clamping force 50T) manufactured by Sumitomo Heavy Industries, Ltd. under conditions of a cylinder temperature of 260°C, a mold temperature (set) of 80°C, and a cooling time of 30 seconds. The maximum mold release resistance value (unit: MPa) when the product was released by ejecting the ejector pin was evaluated as the mold release resistance. For the measurement, a mold merger system (registered trademark) was used, which uses an ejector pin-shaped pressure sensor (EP Sensor (registered trademark)) with a built-in pressure sensing element manufactured by Futaba Corporation. The unit is MPa.
[0115] [Table 2]
[0116] As is clear from the above results, the resin composition of the present invention had a short glowing time and excellent releasability (Example 1). In particular, it had a shorter glowing time and excellent releasability than Comparative Example 3 containing PTFE. In contrast to this, when a release agent other than polyolefin wax was used (Comparative Examples 1 and 2), the glowing time was long and the releasability was poor, regardless of whether PTFE was included or not. Moreover, in Comparative Example 3, when PTFE was simply removed, the glowing time became longer and the releasability was further deteriorated (Comparative Example 2).
Claims
1. For a total of 100 parts by mass of 10 to 90 parts by mass of polyalkylene terephthalate resin and 90 to 10 parts by mass of styrene-based resin, 0.5 to 45 parts by mass of a flame retardant; and 0.01 to 10 parts by mass of polyolefin wax; A resin composition that is substantially free of fluoropolymers.
2. The resin composition according to claim 1, wherein the polyalkylene terephthalate resin has an intrinsic viscosity of 0.40 to 1.2 dL / g.
3. The resin composition according to claim 1, wherein the polyalkylene terephthalate resin has an intrinsic viscosity of 0.40 to 0.85 dL / g.
4. The resin composition according to claim 1, wherein the polyalkylene terephthalate resin has an intrinsic viscosity of 0.40 to 0.80 dL / g.
5. The resin composition according to any one of claims 1 to 4, wherein the polyalkylene terephthalate resin comprises a polybutylene terephthalate resin.
6. The resin composition according to any one of claims 1 to 4, wherein the flame retardant comprises a brominated flame retardant.
7. The resin composition according to any one of claims 1 to 4, wherein the polyolefin wax comprises a polyethylene wax.
8. The resin composition according to any one of claims 1 to 4, further comprising a compatibilizer.
9. The resin composition of claim 8 , wherein the compatibilizer comprises a polycarbonate resin.
10. The polyalkylene terephthalate resin has an intrinsic viscosity of 0.40 to 0.80 dL / g; the polyalkylene terephthalate resin comprises a polybutylene terephthalate resin; The flame retardant comprises a brominated flame retardant, The polyolefin wax comprises a polyethylene wax, Further comprising a compatibilizer, The resin composition of claim 1 , wherein the compatibilizer comprises a polycarbonate resin.
11. A pellet of the resin composition according to any one of claims 1 to 4 and 10.
12. A molded article formed from the resin composition according to any one of claims 1 to 4 and 10.
13. A molded article formed from the pellets of claim 11.
Citation Information
Patent Citations
Thermoplastic resin composition and molded article
JP2020176158A